PARTICIPATION OF THE SERBIAN ARMED FORCES IN EUROPEAN UNION COMMON SECURITY AND DEFENCE POLICY MISSIONS AND OPERATIONS - Prodanić, Vanja (National interest, 2023)
This research is an attempt to review and analyze the available literature and documentation in order to get insight into involvement of the Serbian Armed Forces in European Union missions and operations, since at the moment the Republic of Serbia engages exclusively military capacities in three European Union missions and operations. Our officers and military doctors represent a significant and visible contribution to the implementation of the European Union Common Security and Defence Policy missions in Somalia and Central African Republic.In 2023 it is expected that Serbian Armed Forces will start its engagement in the European Union training mission in Mozambique – EUTM Mozambique, so as in the European Union Combat Group HELBROC. Those engagements are significant expansion in participation in missions and operations under the European Union Common Security and Defence Policy, and will further increase the reputation that the Republic of Serbia have gained on the international political scene, in the field of peacekeeping.Further more, there is an obvious space for improvement of the current level of cooperation that the Republic of Serbia is achieving with the European Union through the joint engagement in missions and operations. One of the obligations arising from the process of accession of the Republic of Serbia to the European Union is the creation of a legal framework for the beginning of engagement of civilian capacities in European Union Common Security and Defence Policy missions and operations. This will be possible as soon as the Republic of Serbia adopt a law that will regulate the participation of civilians in peacekeeping operations outside our national borders. It is expected that the engagement of civilian capacities within the European Union Civilian peace support missions will have a positive effect on the reputation of the Republic of Serbia in the field of preserving global peace and security.The goal of the research is the description and explanation of the current engagement of the Serbian Armed Forces in European union missions and operations, which can be of importance both to decision-makers of the Republic of Serbia regarding the future engagement of military and civilian capacities within the European Union Common Security and Defence Policy missions and operations, so as to citizens, in order to gain a more complete insight into this matter.
Keywords: missions and operations; crisis focus; Serbian Armed Forces; Common Security and Defense Policy; European Union